2020
DOI: 10.1002/aenm.201903191
|View full text |Cite
|
Sign up to set email alerts
|

Electron‐Beam‐Related Studies of Halide Perovskites: Challenges and Opportunities

Abstract: Electron beam microscopy and related characterization techniques play an important role in revealing the microstructural, morphological, physical, and chemical information of halide perovskites and their impact on associated optoelectronic devices. However, electron beam irradiation usually causes damage to these beam-sensitive materials, negatively impacting their device performance, and complicating this interpretation. In this article, the electron microscopy and spectroscopy techniques are reviewed that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 157 publications
(212 reference statements)
0
66
0
Order By: Relevance
“…However, this is very challenging when dealing with organic–inorganic nanocomposites, such as hybrid halide perovskites, as such materials are prone to beam damage when subjected to high‐intensity electron bombardment. [ 8–11 ] Previous research has shown that the primary beam damage mechanism for hybrid perovskites is radiolysis or ionization damage which causes bond breaking and disintegration of the perovskite crystal structure. [ 12,13 ] Possible results of radiolysis include formation of vacancies through atomic/ionic displacement and loss of volatile molecules.…”
Section: Beam Current [Pa] Dose Rate [E− å−2 S−1] Dwell Time [Ms] Dosmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is very challenging when dealing with organic–inorganic nanocomposites, such as hybrid halide perovskites, as such materials are prone to beam damage when subjected to high‐intensity electron bombardment. [ 8–11 ] Previous research has shown that the primary beam damage mechanism for hybrid perovskites is radiolysis or ionization damage which causes bond breaking and disintegration of the perovskite crystal structure. [ 12,13 ] Possible results of radiolysis include formation of vacancies through atomic/ionic displacement and loss of volatile molecules.…”
Section: Beam Current [Pa] Dose Rate [E− å−2 S−1] Dwell Time [Ms] Dosmentioning
confidence: 99%
“…[ 19 ] Further, it indicates that dose rate has minimum impact on beam damage, as previous works conducted with parallel beam TEM‐EDX also observed a similar decline of I/Pb ratio in MAPbI 3 . [ 9,10,14 ] We note that factors other than total dose may affect the extent of radiolysis, such as electron beam energy or sample thickness (or surface/volume ratio). [ 13 ] Here both are nominally constant, so have been disregarded from the analysis.…”
Section: Beam Current [Pa] Dose Rate [E− å−2 S−1] Dwell Time [Ms] Dosmentioning
confidence: 99%
“…A focused electron beam (e-beam) provided in a scanning electron microscope (SEM) or transmission electron microscope (TEM) can also be used to regulate crystal structures, as well as optoelectronic properties of materials [39][40][41]. Although a single-crystal MAPbBr 3 microplate photodetector with increased photocurrent has been fabricated through direct e-beam exposure, it is widely accepted that e-beam irradiation can significantly degrade perovskite structures as well as the PL emission [42,43]. Therefore, how electrons affect or interact with OIHPs is still an open question.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Structural, chemical, electronic, and dynamic properties at this scale are accessible with transmission electron microscopy (TEM), but the stability of HOIPs is such that electron-beam damage can be significant. [4][5][6][7] Indeed, sensitivity of HOIPs to even low dose rates may limit what can be learned about fundamental structure/function relationships. [8][9][10] This damage is thought to occur through a combination of charging, ionic excitation, and heating leading to ion migration and separation of the organic and inorganic constituents.…”
mentioning
confidence: 99%
“…Beam-damage mechanisms in TEM are numerous and often synergistic, necessitating detailed design and systematic execution of experiments. 4,23 Conveniently, fs pulsed lasers in a stable lab environment afford high levels of control, enabling accurate and precise quantification of pulsed TEM beam damage. 17 An overview of the fs laser-driven approach used here, and the method for quantifying damage to MAPbI3 specimens, is shown in Figure 1.…”
mentioning
confidence: 99%